Genetic Characterization and Sequencing of Lumpy Skin Disease Virus Isolate Circulating in Beni-Suef Governorate, Egypt - Lutfi Mohamed Mohamed Bakar; Hosein Abd al Aal; Sabry Mohamed Tammam; Hanafy Mahmud Madbouly (African Journal of Advanced Pure and Applied Sciences, 2024)
Large outbreaks of skin lesions in cattle have been observed recently throughout the governorate. The LSDV was shown to be the causative factor. The local strain of LSDV was sequenced and deposited into GenBank, where it was assigned the accession number MK552139 and designated as LSDV/Egy-BSU/2018. The discovered strain resources were connected and to other LSDVs, however the phylogenetic tree clustered viruses of sheep pox, goat pox, and LSD viruses independently. The GPCR gene nucleotide and the LSDV’s inferred amino acid sequences were examined in this work by comparing them to the corresponding reference sequences found in the GenBank.